Pre-conception Health Behaviors among Female Collegians Students: Perilaku Kesehatan Pra-Konsepsi di Kalangan Mahasiswa Perempuan - Arief, Nawres Jameel; Naji, Arkan Bahlol (Universitas Muhammadiyah Sidaorjo, 2023)
This study explores preconception health behaviors among female college students at the University of Baghdad's College of Languages, English Department, highlighting a significant gap in health-promoting activities prior to pregnancy. Despite the general understanding of the importance of pre-pregnancy health, there is limited research focusing on the predictive factors influencing these behaviors among university students. The study, conducted from October 1, 2023, to March 11, 2024, involved 144 female students selected through non-probability sampling. Data were collected via a validated 5-point Likert scale and analyzed using descriptive and inferential statistics. Findings indicate that 74.4% of participants exhibited low levels of preconception health behaviors, with age, academic grade, and socioeconomic status being significant factors. These results underscore the need for targeted educational interventions to enhance pre-pregnancy health awareness and behaviors among female college students, potentially improving outcomes for future maternal and child health. Keywords: Pre-conception, Health Behaviors, Female Collegians